2018
DOI: 10.1080/23273798.2018.1476727
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in decoding skill, print exposure, and cortical structure in young adults

Abstract: This exploratory study investigated relations between individual differences in cortical grey matter structure and young adult readers’ cognitive profiles. Whole-brain analyses revealed neuroanatomical correlations with word and nonword reading ability (decoding), and experience with printed matter. Decoding was positively correlated with grey matter volume (GMV) in left superior temporal sulcus, and thickness (GMT) in right superior temporal gyrus. Print exposure was negatively correlated with GMT in left inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 153 publications
(238 reference statements)
1
27
2
1
Order By: Relevance
“…Also in adults, He et al (2013) reported positive correlations between gray matter volume in the left SMG and precuneus with phonological decoding in Chinese speakers with English as a second language performing English reading tests (n = 416). A relationship between reading ability and gray matter volume in left STS, SMG, and MTG, as well as diffuse bilateral frontal and parietal regions, have been reported by Johns et al (2017) (n = 35), whereas a relationship with gray matter volume in left FG has been reported by Torre and Eden (2019) , both studies conducted in adult readers of English. Taken together, it seems that relationships between gray matter volume and reading ability are more evident in adults than children.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Also in adults, He et al (2013) reported positive correlations between gray matter volume in the left SMG and precuneus with phonological decoding in Chinese speakers with English as a second language performing English reading tests (n = 416). A relationship between reading ability and gray matter volume in left STS, SMG, and MTG, as well as diffuse bilateral frontal and parietal regions, have been reported by Johns et al (2017) (n = 35), whereas a relationship with gray matter volume in left FG has been reported by Torre and Eden (2019) , both studies conducted in adult readers of English. Taken together, it seems that relationships between gray matter volume and reading ability are more evident in adults than children.…”
Section: Introductionmentioning
confidence: 92%
“…In contrast, a third, also in English speakers (n = 60), found a positive relationship between cortical thickness of the left IPS, bilateral AG, and bilateral STG with performance on a task of irregular word reading, as well as a negative relationship between cortical thickness of the left central sulcus and FG, bilateral IFG and right lingual and supramarginal gyri with irregular word reading ( Blackmon et al, 2010 ). The fourth study, also in English speakers (n = 35), found a positive relationship between cortical thickness of the right STG, precentral, lateral occipital cortices with single word reading ( Johns et al, 2017 ). One of these studies measured surface area in addition to cortical thickness and reported a negative relationship between surface area and single real word reading in the left FG ( Frye et al, 2010 ).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, for cortical thickness analyses, no covariates were used, as suggested by previous researchers (e.g., Westman et al, 2013). Monte Carlo simulations were used to correct all vertex-wise results at an individual vertex level of p < 0.05 (Hagler et al, 2006; see also Johns et al, 2018…”
Section: Magnetic Resonance Imaging: Processing and Between-sex Statimentioning
confidence: 99%
“…Second, we employ a community-based sample with 285 greater variability in linguistic and cognitive abilities, as well as demographics, than typical 286 psycholinguistic samples, potentially providing a more representative picture of reading-related 287 ability in the population and enhancing statistical power for investigating individual differences 288 (cf. Braze et al, , 2007Johns et al, 2018;Johns, Matsuki, & Van Dyke, 2015;Kukona et 289 al., 2016;Van Dyke, Johns, & Kukona, 2014). By comparing individuals' online speech 290 processing to outcome measures of phonological skills more typically used in reading research, 291 we aim to probe the relationship between phonological representations and phonological skills 292 (see Ramus et al, 2013 decoding and reading comprehension).…”
Section: The Current Studymentioning
confidence: 99%